2021
DOI: 10.1101/2021.02.15.431225
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Topoisomerase VI is a chirally-selective, preferential DNA decatenase

Abstract: DNA topoisomerase VI (topo VI) is a type IIB DNA topoisomerase found predominantly in archaea and some bacteria, but also in plants and algae. Since its discovery, topo VI has been proposed to be a DNA decatenase, however robust evidence and a mechanism for its preferential decatenation activity was lacking. Using single-molecule magnetic tweezers measurements and supporting ensemble biochemistry, we demonstrate that Methanosarcina mazei topo VI preferentially unlinks, or decatenates, DNA crossings, in compari… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 80 publications
(121 reference statements)
0
3
0
Order By: Relevance
“…As suggested by recent biochemical studies, this may be linked to specific substrate recognition. The proposition of TopoVI binding to DNA crossing is interesting with respect to the topological status of sister chromatids after DNA replication (McKie et al ., 2022) and some factors may tether TopoVI to replication forks or intermediates. Understanding these TopoVI biochemical properties might also help to elucidate TopoVIL activity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As suggested by recent biochemical studies, this may be linked to specific substrate recognition. The proposition of TopoVI binding to DNA crossing is interesting with respect to the topological status of sister chromatids after DNA replication (McKie et al ., 2022) and some factors may tether TopoVI to replication forks or intermediates. Understanding these TopoVI biochemical properties might also help to elucidate TopoVIL activity.…”
Section: Resultsmentioning
confidence: 99%
“…As A. thaliana TopoVIA/B mutants are defective in endoreduplication, it was proposed that the TopoVI decatenation activity is involved in resolving catenated chromatids generated by endoreduplication. In fact, although TopoVI possesses both relaxation and decatenation activities, it was shown that Methanosarcina mazei TopoVI is preferentially a decatenase in vitro (McKie et al, 2022). Interestingly, the functional link with DNA replication is also supported by the interaction detected by immunoprecipitation between Pyrococcus abyssi TopoVI and the replication fork components PCNA, NusC and RFC (Ren et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation